Dividend Payments and Share Price Behaviour of Selected Manufacturing Firms in Nigeria - Oyedele, Adesoji Iyiola; Afolabi, Taofeek Sola (Archives of Business Research, 2024)
Share price behaviour is affected by information relating to corporate earnings of a firm which is vital to investors and analysts. The behaviour becomes more unpredictable when information on dividends payment is made available to the stock market. Studies have been carried out on the performance of the stock market but there remains no consensus on the effects of dividend payments on share price behaviour of listed manufacturing firms in Nigeria. This study adopted ex-post facto research design involving annual data covering 2013 to 2022 time frame and across the 14 listed selected manufacturing firms. The data were obtained from Nigeria Exchange Limited and audited published financial reports of the selected firms. The study deployed System Generalised Method of Moments (SGMM). Estimates of the coefficients of the model were evaluated at 5% level of significance. The results showed that dividend per share had significant positive effect on. In addition, earnings per share exerted positive and significant effect on share price behaviour. Furthermore, firm size had positive, but insignificant effect on share price behaviour. The study concluded that corporate dividend payment is key determinant of share price behaviour of manufacturing firms listed in Nigeria and that earnings per share and share price behaviour reinforced each other. Thus, the study recommended that the management of listed manufacturing firms in Nigeria should intensify the use of dividends as strategies to attract investors into the sector in order to reposition themselves as preferred investment destinations.